ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM IN CLASS VI OF ELEMENTARY SCHOOL 07 BENGKULU CITY - Sapruni, Sapruni; Al Fauzan Amin; Rohimin, Rohimin; Suradi, Ahmad; Aprianti, Nefi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study was to determine and examine the